Reduction of deoxynivalenol, T-2 and HT-2 toxins and associated Fusarium species during commercial and laboratory de-hulling of milling oats - Jens C. Meyer; Tim Birr; Inga Hennies; Detlev Wessels; Karin Schwarz (Food Additives & Contaminants: Part A, 2022)

Selection of bacteria and fungi for control of soilborne seedling diseases of maize - Tobias Pfeiffer; Astrid von Galen; Petra Zink; Sebastian Hübner; Ada Linkies; Dieter Felgentreu; Jannika Drechsel; Tim Birr; Olaf Röder; Mathias Kotte; Kristin Dietel; Helmut Junge; et al. (Journal of Plant Diseases and Protection, 2021)
Plant-based screening experiments were conducted with the aim of identifying biocontrol bacteria and fungi for seed treatment of maize. Candidate microorganisms were evaluated for their protective effects against soilborne infections by species of Fusarium , Globisporangium (syn. Pythium ) and Rhizoctonia. The microorganisms tested were bacteria and fungi from maize roots or other sources, including some active microbial components of commercial biocontrol products. Due to the method of isolation chosen, the majority of bacteria from maize roots were spore formers, most of them species of the genera Bacillus, Brevibacillus and Paenibacillus . In pot tests with the potting substrate inoculated with F. culmorum, the level of control provided by seed treatment with the most efficacious bacterial and fungal isolates was comparable or close to the chemical reference seed treatment thiram. The most effective bacteria were species of Pseudomonas , Burkholderia and Streptomyces . Among a subset of approx. 100 bacteria studied, the in vivo and in vitro activities against F. culmorum were only weakly correlated, although some strains deviated from this pattern. The most effective fungi were two strains of Clonostachys rosea and isolates of Trichoderma . The latter and a strain of Gliocladium virens provided also protection against R. solani . Activity against Globisporangium ultimum was recorded for one isolate of Trichoderma and the two strains of C. rosea. A reduction in the impact of seedborne F. culmorum was also observed after seed treatment with two strains of F. oxysporum f. sp. strigae. The results are discussed in relation to previous reports on rhizosphere bacteria of maize and their use in biocontrol of plant pathogens or for plant growth promotion.

Artificial inoculation methods for testing microorganisms as control agents of seed- and soil-borne Fusarium-seedling blight of maize - Eckhard Koch; Petra Zink; Tobias Pfeiffer; Astrid von Galen; Ada Linkies; Jannika Drechsel; Tim Birr (Journal of Plant Diseases and Protection, 2020)
The study describes the development and employment of plant tests based on artificial inoculation of seeds or the potting substrate for evaluating the potential of microorganisms to control seedling blight of maize caused by seed- and soil-borne fusaria. Nine strains of Fusarium were isolated from maize kernels and identified morphologically and by molecular methods as belonging to the species Fusarium verticillioides, F. subglutinans, F. cerealis, F. poae and F. proliferatum . In order to determine pathogenicity, maize kernels were inoculated by immersion in suspensions of conidia of these isolates and sown in a pasteurized substrate in seed trays. Based on plant dry weight, the isolates of F. verticillioides and F. subglutinans were more pathogenic than the other isolates. Using an isolate of F. subglutinans , the efficacy of a set of 25 potential fungal and bacterial antagonists was assessed using inoculation of maize kernels by placement in mixtures of the pathogen and the antagonists. The results obtained with this methodology indicate the potential of a number of different microorganisms applied as seed treatments, including some reported previously as biocontrol agents, to control seed-borne seedling blight of maize. In order to develop a method for the testing of biocontrol agents against soil-borne attack, isolates of F. subglutinans , F. cerealis and F poae from maize kernels together with isolates of F. avenaceum , F. culmorum and F. graminearum originating from maize silage and wheat were used to artificially inoculate the potting substrate. The results showed large differences in pathogenicity, with the most aggressive isolates belonging to F. culmorum and F. graminearum.

Effect of ensiling duration on the fate of deoxynivalenol, zearalenone and their derivatives in maize silage - Tolke Jensen; Marthe De Boevre; Sarah De Saeger; Nils Preußke; Frank D. Sönnichsen; Ewald Kramer; Holger Klink; Joseph-Alexander Verreet; Tim Birr (Mycotoxin Research, 2020)

Prediction of deoxynivalenol and zearalenone in winter wheat grain in a maize-free crop rotation based on cultivar susceptibility and meteorological factors - Tim Birr; Joseph-Alexander Verreet; Holger Klink (Journal of Plant Diseases and Protection, 2019)